(3x+y)-(-x-4y) (х+6у)-(8х-7у) (m+n)-(m-n) (m+3)-(6m+5)-(m-1) (x-y)+(x-y)-(2x+y) (0,2x-3)-(x-2)-(0,4x-1) Жақшаны ашып өрнекты ықшамдау керек

(3x+y)-(-x-4y) (х+6у)-(8х-7у) (m+n)-(m-n) (m+3)-(6m+5)-(m-1) (x-y)+(x-y)-(2x+y) (0,2x-3)-(x-2)-(0,4x-1) Жақшаны ашып өрнекты ықшамдау керек
Гость
Ответ(ы) на вопрос:
Гость
1)(3x+y)-(-x-4y)=4x+5y 2)(x+6y)-(8x-7y)=-7x+13y 3)(m+n)-(m-n)=2n 4)(m+3)-(6m+5)-(m-1)= -1-6m 5)(x-y)+(x-y)-(2x+y)=-3y 6)(0,2x-3)-(x-2)-(0,4x-1)=-1,2x Солай ма?
Не нашли ответ?
Ответить на вопрос
Похожие вопросы